Pemberdayaan Masyarakat Dalam Pembangunan Pariwisata Desa Gadingan yang Berkelanjutan - Amilia, Winda; Fatimatuzzahro, Nadie; Suryaningrat, Ida Bagus; Suryadharma, Bertung; Permana Shita, Amandia Dewi (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2024)
Tourism is a human activity that utilizes natural resources for recreational needs. It is without considering long term sustainability can damage nature and be detrimental to human life. Gadingan Village in Situbondo Regency is building a spring tourist destination called Gadingan Mas. Pokdarwis efforts in the construction of Gadingan Mas are constrained by the lack of public awareness to preserve the environment , which is indicated by the use of springs for toilet activities by some communities and the disposal of garbage around waterways. The principle of sustainability in the triple bottom line was adopted by socializing the development of clean Gadingan Mas tourism, so that it is useful and brings profit to the community. The method of implementation is by counseling the importance of maintaining environmental health, socializing environmental sanitation to the community around tourism and providing hygiene facilities. The results of the activity show the use of cleaning facilities that show awareness and cleanliness. The sustainability of Gadingan Mas tourism is supported by public awareness of cleanliness which encourages an increase in the number of tourists in Gadingan mas tourism.